The Effectiveness of Using Movies “Frozen” to Improve Students Vocabulary In Pandemic Covid 19 - Aguslina Giawa; Fara Fadhila; Mia Audina Simbolon; Madina Madina (Jurnal Ilmiah Wahana Pendidikan, 2021)
The formation of vocabulary is an important part of any language learning process. The most crucial language feature for students to master is vocabulary, since it is the key to understanding what they hear and read and then speaking effectively with others. The researcher evaluates the effectiveness of one of the alternative teaching methodologies using the film "FROZEN." It's an opportunity for them to improve their memorization abilities. The study's goals are to determine if students' vocabulary improves after viewing movies by taking a test. Watching films in Indonesian, English, and without subtitles helps students enhance their language skills. According to the post test findings, There were 14 students who received excellent scores on the second pretest (score: 80- 100). It can be stated as a percentage: 77,77% of students receive excellent grades. Students who receive good grades are 9 students (score 70- 79). 22,23% of students can earn good grades, which may be expressed as a percentage. The students received an overall score of 1555. The overall average is 86.38. The Standar Derivation is 8.88. We can see from the three outcomes above that studying through films can help students enhance their vocabulary. Several elements impact students' capacity to acquire vocabulary utilizing the "FROZEN" movie watching approach, including their interest in watching, facilities at school or employed by English teachers, student motivation, and appropriate time. Students have been taking virtual lessons (online classes) because to the covid-19 epidemic till today. Virtual classrooms, in the opinion of students, are less effective for learning English, especially when students study vocabulary by using the zoom application to view the Frozen movie. Keywords : Improving, Vocabulary, Using movie.